Tai Chi for improvement of motor function, balance and gait in Parkinson's disease: a systematic review and meta-analysis. - Yan Yang; Xiang-Yuan Li; Li Gong; Yun-Liang Zhu; Yan-Lei Hao (PLoS ONE)
Background Recently, several studies assessed the effectiveness of Tai Chi for Parkinson's disease (PD), but the role of Tai Chi in the management of PD remained controversial. Therefore, the purpose of this systematic review is to evaluate the evidence on the efficacy of Tai Chi for PD. Methods Six English and Chinese electronic databases, up to April 2014, were searched to identify relevant studies. The risk of bias in eligible studies was assessed by Cochrane Collaboration's tools. The primary outcomes were motor function, balance and gait in individuals with PD. Standardized mean difference (SMD) and 95% confidence intervals (CI) of random-effect model were calculated. And heterogeneity was assessed based on the I2 statistic. Results 7 randomized controlled trials and 1 non-randomized controlled trial were eligible. The aggregated results suggested that Tai Chi showed beneficial effects in improving motor function (SMD, -0.57; 95% CI -1.11 to -0.04; p = 0.03), balance (SMD, 1.22; 95% CI 0.80 to 1.65; p<0.00001) and functional mobility (SMD, 1.06; 95% CI 0.68 to 1.44; p<0.00001) in patients with PD, but not in improving gait velocity (SMD, -0.02; 95% CI -0.58 to 0.54; p = 0.94), step length (SMD, -0.00; 95% CI -0.57 to 0.56; p = 0.99), or gait endurance (SMD, 0.53; 95% CI -0.07 to 1.12; p = 0.08). Comparing with other active therapies, however, Tai Chi only showed better effects in improving balance (SMD, 0.74; 95% CI 0.38 to 1.10; p<0.0001). Conclusion Tai Chi should be a valid complementary and alternative therapy for PD, especially in improving motor function and balance. However, more studies with long follow-up are warrant to confirm the current finding of Tai Chi for PD.